Pendidikan Islam Antiradikalisme Melalui Sifat Feminim Allah, Local Wisdom, Dan Political Will - Murjiah; Hamdan; Husnul Yaqin; Hidayat Ma'ruf (Jurnal Pendidikan Agama Islam, 2026)
Intolerance, radicalism, and terrorism are serious threats to religious and national life in Indonesia. Islamic education plays a strategic role in preventing and countering these phenomena. This article examines strategies to prevent intolerance, radicalism, and terrorism through three integrative approaches: (1) the approach of Allah’s feminine attributes (al-Asma’ al-Husna), emphasizing compassion, gentleness, and mercy; (2) the local wisdom approach, highlighting Indonesian cultural values as an ideological safeguard; and (3) the political will approach, reflecting the government’s commitment to strengthening the role of Islamic educational institutions. This study employs library research using a qualitative-descriptive approach. The findings reveal that these three approaches synergistically contribute to shaping students with moderate, tolerant, and peace-loving characters, thereby protecting them from radical ideologies and acts of terrorism.